Occupational and individual factors in acute shoulder-neck disorders among industrial workers. Issue 4 (November 1981) - Bjelle, A; Hagberg, M; Michaelson, G
Abstract : Twenty workers, consecutively attending the industrial health care centre for the first time with acute shoulder-neck pains, were subject to extensive rheumatological and ergonomic examinations. In seven patients congenital malformations for diseases causing musculoskeletal symptoms, or both, were probable aetiological factors. In the remaining 13 patients a significantly higher load was found on both shoulders (assessed by biomechanical film analysis) than in matched control. Age, anthropometric measures, muscle strength, or HLAB27 did not appear as significant predisposing factors. Most patients could return to work within a year.